Asymmetry and the problem of aggregation in the euro area - David G. Mayes; Matti Virén (Bank of Finland, 2000)
This paper highlights the implications for EU macroeconomic policy at a relatively disaggregated level when key economic relationships are nonlinear or asymmetric.Using data for the EU and OECD countries we show that there are considerable non-linearities and asymmetries in the Phillips and Okun curves.High unemployment has a relatively limited effect in pulling inflation down while low unemployment can be much more effective in driving it up.Downturns in the economy are both more rapid and sustained in driving unemployment up than recoveries are in bringing it down.There is considerable variety in these relationships and in IS curves across not just countries but also sectors and regions.
URN:NBN:fi:bof-20140807137
Keywords: 330; aggregation; asymmetry; monetary policy; nonlinear models; Okun curve; Phillips curve